Orthodontic Treatment of Severe Crowding Malocclusion with Extraction of premolars. (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Space deficiency in a crowded dentition is a main indication for premolar extraction therapy. Class I malocclusions with severe crowding in non growing patients can be treated by upper lower first premolar extraction using an edgewise technique with multi loop edgewise arch wire (MEAW). The following case report describes a patient with severe tooth crowding, where the result of the treatment was acceptable and relatively stable. It was concluded that the elimination of tooth tissue discrepancy by the extraction of first premolars provides a good means in the treatment of crowding malocclusions. DOI: http://dx.doi.org/10.3329/bjodfo.v2i2.16161 Ban J Orthod & Dentofac Orthop, April 2012; Vol-2, No.2, 30-33